Online Survey of Reading Strategies (OSORS): students’ Online reading in academic context - Jusoh, Zailani; Abdullah, Liza (Penerbit Universiti Sains Malaysia, 2015)
Academic success greatly depends on the ability of students to capitalise the information available at their disposal through improved reading skills. However, the emergence of digital texts has transformed the nature of academic reading as online reading is reported to be different from traditional printed reading. As such, this paper which is based on a study conducted on students in a particular university in Malaysia, was written to investigate the extent of the use of strategies when reading online, in an academic setting and also to investigate whether differences in the use of the strategies between students in different field of studies exist. Findings suggest that students are all users of strategies and field of studies has no bearing on the type of overall strategies preferred. However, significant difference was found for support strategies. One of the implications is the need for class instruction in raising students’ awareness on the importance of varied usage of strategies when reading materials online